âRELASI PENGUASA-PENGUSAHA DI BUMI ANTASARIâ (Studi Kasus: Aktifitas Pertambangan Emas hitam di Kabupaten Kotabaru Provinsi kalimantan Selatan) - , MAULIDYA WIDIARTI, Miftah Adhi Ikhsanto, Mi.OP. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This case study purpose to explain about government and business relationship, as the key actor for exploitation system of coal resources, in Kotabaru district, South Kalimantan province. How the formal actor (government) have seized opportunity to increase their own-source revenue by issuing numerous coalmining permits and at the same time their decision was support the informal economy access to eliminated formal authority. All obtained information through the interview and library research method with explanative analyses. The gist of oneâs thoughts 1) Existence of strong connection between local political figure and businessmen